Implementasi dan Strategi Pengembangan Digital Marketing pada UMKM di Desa Sinarsari, Kecamatan Dramaga, Kabupaten Bogor - Bunga Fariza Hamid; Fairuz Syifa Hidayat; Nurshadrina Alifah Sajidah; Taufik Hidayat; Agief Julio Pratama; M. Iqbal Nurulhaq; Tri Budiarto; Widya Hasian Situmeang; Ratih Kemala Dewi; Restu Puji Mumpuni; Edi Wiraguna (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Digital marketing plays a crucial role in enhancing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in the digital era. This study aims to analyze the extent of digital marketing implementation by MSMEs in Sinarsari Village and to design strategies for improving entrepreneurs' capabilities in optimizing digital marketing. The research uses a mixed-method approach, combining both qualitative and quantitative methods. The findings reveal that most MSMEs have utilized digital platforms such as social media, messaging apps, and online marketplaces to promote their products. The implementation of digital marketing has proven effective in increasing product visibility, expanding market reach, boosting sales, and improving income. However, several challenges remain, including limited technological knowledge and a lack of understanding of effective branding. Therefore, training programs and mentoring are necessary to help MSME actors optimize their digital marketing strategies. With a more strategic and effective application of digital marketing, MSMEs can grow sustainably and strengthen their position in both the local and national economy.